2010
DOI: 10.1614/ws-d-10-00012.1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cultivar, Planting Pattern, and Weed Management Tactics in Peanut

Abstract: Planting peanut in narrow rows for weed control has not been investigated in recently released Virginia market peanut cultivars. Research was conducted in North Carolina from 2007 to 2009 to determine the effect of cultivar, planting pattern, and level of weed management inputs on weed control, peanut yield, and estimated economic return. Experiments consisted of three levels of weed management (clethodim applied POST, cultivation and hand-removal of weeds, and clethodim and appropriate broadleaf herbicides ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Crop cultivars that mature at different rates or have different competitive abilities may be used to suppress weed populations and weed growth (Froud-Williams 1988;Richards 1989). Use of competitive crop cultivars has been examined in crops as varied as vegetables and grains in organic crop production (Barberi 2002), soybean (Nordby et al 2007), canola (Beckie et al 2008;Harker et al 2003), wheat (Wicks et al 2004), peanut (Arachis hypogaea L.) (Place et al 2010), rice (de Vida et al 2006;Gealy et al 2003), and potatoes (Solanum tuberosum L.) (Colquhoun et al 2009). Factors affecting competitive ability include height, density, leaf area, tillering, canopy type, allelopathic potential, and cultivar differences in competition for light, water, and soil nutrients (Grundy et al 1992;Lotz et al 1991;Moss 1985;Pyšek and Lepš 1991;Richards and Whytock 1993;Standifer and Beste 1985).…”
mentioning
confidence: 99%
“…Crop cultivars that mature at different rates or have different competitive abilities may be used to suppress weed populations and weed growth (Froud-Williams 1988;Richards 1989). Use of competitive crop cultivars has been examined in crops as varied as vegetables and grains in organic crop production (Barberi 2002), soybean (Nordby et al 2007), canola (Beckie et al 2008;Harker et al 2003), wheat (Wicks et al 2004), peanut (Arachis hypogaea L.) (Place et al 2010), rice (de Vida et al 2006;Gealy et al 2003), and potatoes (Solanum tuberosum L.) (Colquhoun et al 2009). Factors affecting competitive ability include height, density, leaf area, tillering, canopy type, allelopathic potential, and cultivar differences in competition for light, water, and soil nutrients (Grundy et al 1992;Lotz et al 1991;Moss 1985;Pyšek and Lepš 1991;Richards and Whytock 1993;Standifer and Beste 1985).…”
mentioning
confidence: 99%
“…In these trials, multiple or narrow row patterns suppressed weed growth, but not enough to reduce herbicide use. It was the general consensus that greater yields and net returns of paired row spacings compared with wide row spacings were due to optimum conditions for crop growth that increased yield, not necessarily improved weed control (Colvin et al 1985;Cox and Reid 1965;Johnson et al 2005;Place et al 2010).…”
mentioning
confidence: 99%
“…A review of the literature documenting studies focused on evaluation of row spacing and row configuration was conducted as a summary of the work conducted in this area over the last three centuries. Figures 1 and 2 show average yields and relative weed abundance reported across the studies found in the literature review (Hauser and Buchanan 1981;Besler 2004;Brecke and Stephenson 2006;Cardina et al, 1987;Colvin et al, 1985a;Colvin et al, 1985b;Culbreath et al, 2008;Lanier et al, 2004a;Lanier et al, 2004b, Place et al, 2010Sconyers et al, 2007;Wehtje et al, 1984;Yoder, 2003), (Scott Monfort, unpublished data, 2012. Blackville, SC: Clemson University, Edisto Research & Education Center).…”
Section: Introductionmentioning
confidence: 99%